Image-guided high-dose-rate interstitial brachytherapy – a valuable salvage treatment approach for loco-regional recurrence of papillary thyroid cancer - Wu, Ning; Zhao, Hongfu; Han, Dongmei; Cheng, Guanghui; Zhao, Zhipeng; Ge, Yuxin (Journal of Contemporary Brachytherapy, 2016)
Purpose : To report the treatment effect of image-guided high-dose-rate (HDR) interstitial brachytherapy for refractory recurrence of papillary thyroid cancer (PTC). Case report: This 66-year-old female presented with recurrence 5 years after thyroidectomy for PTC. Despite external irradiation and radioactive 131I, the lesion expanded as 3.7 × 3.0 × 2.3 cm3 and 2.0 × 1.5 × 1.5 cm3. The locoregional recurrent tumor was treated with image-guided HDR interstitial brachytherapy. The total dose of 30 Gy in 6 fractions were delivered on the whole recurrent tumor. Results: Removal of the recurrent tumor was securely achieved by HDR interstitial brachytherapy guided with ultrasound, computed tomography (CT), and magnetic resonance imaging (MRI) scanning. The refractory tumor in the patients healed uneventfully after HDR interstitial brachytherapy without recurrence during the 14 months of follow-up. Conclusions : The image-guided HDR interstitial brachytherapy may be a valuable salvage treatment approach for refractory recurrence of PTC.